2000
DOI: 10.1152/ajpcell.2000.278.5.c905
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and PGE2 regulate activity of apical 70 pS K+ channel in thick ascending limb of rat kidney

Abstract: Vasopressin and prostaglandin E(2) (PGE(2)) are involved in regulating NaCl reabsorption in the thick ascending limb (TAL) of the rat kidney. In the present study, we used the patch-clamp technique to study the effects of vasopressin and PGE(2) on the apical 70 pS K(+) channel in the rat TAL. Addition of vasopressin increased the channel activity, defined as NP(o), from 1.11 to 1.52 (200 pM) and 1.80 (500 pM), respectively. The effect of vasopressin can be mimicked by either forskolin (1-5 microM) or 8-bromo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…The COX-dependent AA metabolites such as PGE 2 have been shown to attenuate the stimulatory effect of vasopressin on Cl reabsorption (7). We have previously demonstrated that PGE 2 at low concentrations (Ͻ1 M) abolished the vasopressin-induced increase in the activity of the apical 70-pS K channel, whereas PGE 2 at high concentrations decreased the activity of the 70-pS K channel by a PKC-dependent mechanism (18). In addition to PGE 2 , the cytochrome P-450-dependent metabolites of AA, such as 20-HETE, have been indicated as potent inhibitors of the Na-K-2Cl cotransporters (9) and the apical 70-pS K channel in the mTAL (27).…”
Section: Discussionmentioning
confidence: 94%
“…The COX-dependent AA metabolites such as PGE 2 have been shown to attenuate the stimulatory effect of vasopressin on Cl reabsorption (7). We have previously demonstrated that PGE 2 at low concentrations (Ͻ1 M) abolished the vasopressin-induced increase in the activity of the apical 70-pS K channel, whereas PGE 2 at high concentrations decreased the activity of the 70-pS K channel by a PKC-dependent mechanism (18). In addition to PGE 2 , the cytochrome P-450-dependent metabolites of AA, such as 20-HETE, have been indicated as potent inhibitors of the Na-K-2Cl cotransporters (9) and the apical 70-pS K channel in the mTAL (27).…”
Section: Discussionmentioning
confidence: 94%
“…PKC is required for angiotensin IIstimulated Na-K-2Cl cotransporter activity (2) and indirectly stimulates Na bicarbonate absorption (14). In addition, a PKC-dependent pathway mediates inhibition of apical K ϩ channel activity caused by high concentrations of prostaglandin E 2 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Short-term regulation of NKCC2 has also been observed and involves effects on both activity and trafficking (18,24,43,44,47). CYP450-and COX-derived metabolites of arachidonic acid (AA) inhibit ion transport in the mTAL by several different mechanisms including interactions with apical K ϩ channels and NKCC2 (32,37,38,52,53). Thus, it is important to understand how molecules that act in the TAL affect AA metabolism since regulation of ion transport in this segment may occur in response to signals induced by receptor activation (20,21,58,60).…”
Section: Discussionmentioning
confidence: 99%